2018
DOI: 10.1167/iovs.18-24497
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Field In Vivo Confocal Microscopy of Meibomian Gland Acini and Rete Ridges in the Eyelid Margin

Abstract: PurposeIn vivo confocal microscopy (IVCM) has been widely used to evaluate changes in the meibomian glands (MGs) in response to age and disease. This study examined the structures described as MGs using wide-field IVCM and laser scanning confocal microscopy (LSCM) in situ and characterized their spatial distribution and localization relevant to the eyelid margin.MethodsIVCM was performed on 30 subjects aged 18 to 38 to visualize structures in the eyelid margin. Size, shape, and distribution characteristics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Thus, the nature of the circularizing stimulus during ocular discomfort may be the consequence of the likely increased friction produced on the ocular surface of subjects with poor tear film quality. This would be consistent with the observation that aging, which is typically accompanied by a more flexible skin, has been associated with a decrease circularity of the papillae in the periorificial region of the Meibomian glands . Nonetheless, other factors, such as an inflammatory pathway, might be involved.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Thus, the nature of the circularizing stimulus during ocular discomfort may be the consequence of the likely increased friction produced on the ocular surface of subjects with poor tear film quality. This would be consistent with the observation that aging, which is typically accompanied by a more flexible skin, has been associated with a decrease circularity of the papillae in the periorificial region of the Meibomian glands . Nonetheless, other factors, such as an inflammatory pathway, might be involved.…”
Section: Discussionsupporting
confidence: 90%
“…With regard to the rest of the parameters measured in the present study, no differences were found among groups. Although commonly misunderstanding the nature of the features typically seen, several previous workers have analysed confocal images from the eyelid. Villani et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations